Design, Synthesis and Docking Studies of a Novel Ciprofloxacin Analogue as an Antimicrobial AGENT. Issue 2 (2012) - Jubie, S.; Kalirajan, R.; Yadav, Pavankumar
Abstract : The carboxylic acid group of ciprofloxacin was modified and amino mercapto triazole was substituted. The compound was confirmed by physical parameters (solubility, melting point), chromatographic methods (TLC) and consistent with its IR & 1 HNMR spectra. The synthesized analogue was screened for antibacterial activity against one gram positive & two gram negative species. The compound exhibited good antibacterial effect towards gram negative species when compared to the standard ciprofloxacin. At the same time the analogue was retaining antibacterial activity towards gram positive species when compared to standard ciprofloxacin. The molecular docking studies showed a good correlation between their antibacterial activity and autodock binding free energy.